Botnfiskundersøkingar i Barentshavet (redusert område) vinteren 1998 - Mehl, Sigbjørn (Havforskningsinstituttet, 1998)
A combined acoustic and bottom trawl survey to obtain indices of abundance and estimates of length and weight at age has been carried out each winter (4-6 weeks in January- March) since 1981 in the Barents Sea. The target species are cod and haddock, but in recent years abundance indices have als0 been worked out for the redfish species and Greenland halibut. Since 1993 the survey area has been extended to the north and east in order to obtain a more complete coverage of the younger age groups of cod. In winter 1997 only the Norwegian part of the Barents Sea was covered, while in 1998 also a small part of the Russian EEZ was included in the investigations. The main results in 1998 were: - cod, haddock and to some extent Greenland halibut were not sufficiently covered due to very limted admittance to Russian EEZ. - all indices as well as lengths and weights at age have been adjusted based on data for Norwegian EEZ 1 total area in 1996, but the adjustments for cod and haddock are inaccurate because the proportions found in the Norwegian EEZ have varied much in recent years. - the abundance indices of 1-4 year old cod were above average or high, while the numbers of 5 year and older fish were lower than in recent years. - the abundance of 1 year old haddock was low, the indices for 2-6 year olds were below average, while the abundances of 7-8 year olds were arnong the highest in the time series - both cod and haddock had low length and weight at age, low weight increment but more normal condition factors. - the indices for S. marinus were a little higher than in 1997 and at or slightly above average leve1 in the time series, while for S. mentella the indices were lower than in in 1997 and below average. - the total abundance index of Greenland halibut increased a little from 1997 to 1998, but recmitment seems weak and the abundances of young age groups (c 5 years) are still very low. NORSK SAMMENDRAG:Eit kombinert akustikk- og botntråltokt med sikte på å framskaffa indeksar for talet på fisk og data for individuell lengde og vekt av kvar aldersgruppe av viktige botnfiskarter er gjennomført kvar vinter (4-6 veker i januar - mars) sidan 1981 i Barentshavet. Hovudinnsatsen er retta mot ungfiskbestandane av torsk og hyse, men i seinare år er slike indeksar også utarbeidde for uerartene og blåkveite. Sidan 1993 er undersøkingsområdet utvida mot nord og aust for å få ei fullstendig dekking av den isfrie delen av utbreiingsområdet til dei yngste årsklassane av torsk. Vinteren 1997 vart bene den norske delen av Barentshavet dekka, medan ein i 1998 fekk tilgang til ein liten del av russisk sone. Resultata for 1998 viser: - torsk, hyse og i nokon grad blåkveite vart mangelfullt dekka p.g.a. stengt russisk sone - alle totalindeksar samt lengder og vekter ved alder er justerte baserte på data for norsk sone 1 totalområdet i 1996, men justeringane for torsk og hyse er usikre sidan den delen av bestandane som er funne i norsk sone har variert ein god del dei siste åra. - 1-4 gruppe indeksane av torsk er over middels og til dels sterke, tala for 5 år og eldre fisk er kraftig redusert og lågare enn på fleire år. - l-gruppe indeksen av hyse er svak, 2-6 gruppa er under middels medan det er bra med 6-7 åringar. - både torsk og hyse har låg lengde og vekt ved alder, låg tilvekst, men bra kondisjon. - begge indeksane for vanleg uer er litt hergare enn i 1997 og på middels nivå eller litt over i tidsserien. - for snabeluer er indeksane under fjorårsnivået og godt under middels i tidsserien. - totalindeksen (botntrål) for blåkveite auka litt frå 1997 til 1998, men det er berre svake teikn til rekruttering og lite fisk mindre enn 40 cm.